(untitled) (Analysis in Theory and Applications, 2016)
Let's take H as an infinite-dimensional Hilbert space and K(H) be the set of all compact operators on H. Using Spectral theorem for compact self-adjoint operators, we prove the Hyers-Ulam stability of Jensen *-derivations from K(H) into K(H).